2017
DOI: 10.3390/molecules22091489
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis, Extraction Optimization, and Biological Evaluation of Cudrania tricuspidata Leaf and Fruit Extracts

Abstract: Cudrania tricuspidata Bureau (Moraceae) shows numerous pharmacological effects and has been used in traditional herbal remedies for inflammation, gastritis, tumors, and liver diseases. However, no validated analytical method for the standardization and optimization of the biological properties of C. tricuspidata preparations has been reported. We developed and validated a reverse-phase high-performance liquid chromatography (HPLC) method for the separation and quantification of active markers. Ethanolic extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
1
42
0
1
Order By: Relevance
“…Additionally, Yoon et al [ 18 ] demonstrated that Quercus acuta extract showed approximately 50% XO inhibitory activity at a concentration of 1 mg/mL. Cudrania tricuspidata extract inhibited XO by approximately 75% at a concentration of 2 mg/mL [ 21 ]. The plant extracts with XO inhibitory activity at 1 and 2 mg/mL demonstrated consistent effects in the in vivo animal disease model.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Yoon et al [ 18 ] demonstrated that Quercus acuta extract showed approximately 50% XO inhibitory activity at a concentration of 1 mg/mL. Cudrania tricuspidata extract inhibited XO by approximately 75% at a concentration of 2 mg/mL [ 21 ]. The plant extracts with XO inhibitory activity at 1 and 2 mg/mL demonstrated consistent effects in the in vivo animal disease model.…”
Section: Resultsmentioning
confidence: 99%
“…Total phenolic content of CTLE was determined according to the method described by Song et al (2017) with minor modifications. Briefly, CTLE (40 mg) was dissolved in 80% methanol (10 mL), and the solution (100 lL) was diluted with distilled water (2.5 mL) and then mixed with Folin-Ciocalteu reagent (100 lL).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Cudrania tricuspidata of the Mulberry family is cultivated in Korea, China, Japan and Russia (Song et al, 2017), and it is commonly called silkworm thorn (Kim & Lee, 2015). Anthocyanin, flavonoids and polyphenols present in the leaves, berries and roots of Cudrania tricuspidata are known to have pharmacological functions, such as anti-inflammation (Oh & Lim, 2011), anti-obesity (Jo et al, 2015) and antioxidant activities (Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They have traditionally been used to prepare fresh juice, jam, wine, vinegar and fermented alcoholic beverages in Korea. Previous studies have reported that the extracts and components of M. tricuspidata fruits have strong antioxidant and free radical-scavenging activities in an in vitro system [22,23]. The antioxidant activity of M. tricuspidata fruit extract is associated with the presence of phenolic compounds such as flavonoids and phenolic acids [17,24].…”
Section: Introductionmentioning
confidence: 99%